An expanded range of catalysts for synthesising biodegradable polyphosphonates. Issue 2 (25th July 2016) - Macdonald, Emily K.; Shaver, Michael P.
Abstract : In this paper we expand the scope of catalysts able to mediate the ring opening polymerisation of the phosphonate monomer 2-methyl-1, 3, 2-dioxaphosphalone-2-oxide. A range of nitrogen bases efficiently catalyse the reaction, each with p K a s of 19 or above; lower p K a bases do not ring open the monomer. Aluminium based catalysts supported by salen and salan ligand frameworks also afford exceptional control, with conversions in excess of 99% and dispersities under 1.1. Together, these studies significantly expand the scope of catalysts to prepare this biodegradable, non-toxic, water soluble polymer. Additionally, we report efforts to expand the monomer scope for these catalysts, showing that altering ring structure and substitution can strongly inhibit productive ring opening.